The association between albumin levels and survival in patients treated with immune checkpoint inhibitors: A systematic review and meta-analysis - Guven, Deniz Can; Sahin, Taha Koray; Erul, Enes; Rizzo, Alessandro; Ricci, Angela Dalia; Aksoy, Sercan; Yalcin, Suayib (Frontiers in Molecular Biosciences, 2022)
Background: Albumin levels may potentially be used as a prognostic biomarker in cancer patients treated with immune checkpoint inhibitors (ICIs) due to its close relationships with nutritional and inflammatory status. Therefore, we conducted a systematic review and meta-analysis to evaluate the association between survival outcomes and albumin levels in patients treated with ICIs. Methods: We conducted a systematic review using the PubMed, Web of Science, and Embase databases to filter the published studies up to 1 June 2022. The meta-analyses were performed with the generic inverse-variance method with a random-effects model. The primary outcome measure was hazard ratio (HR) with 95% confidence intervals (CI). Results: Thirty-six studies encompassing 8406 cancer patients with advanced disease were included in the meta-analyses. Patients with lower albumin levels had significantly increased risk of death (HR: 1.66, 95% CI: 1.52-1.81, p<0.0001) than patients with higher albumin levels. Similarly, the patients with lower albumin levels had increased risk of progression or death compared to patients with higher albumin levels (HR: 1.74, 95% CI: 1.39-2.17, p<0.001). Conclusion: The available evidence demonstrates that albumin levels may be a prognostic biomarker in advanced cancer patients treated with ICIs.